Observational Evidence of Shallow Origins for the Magnetic Fields of Solar Cycles - Martin, Sara F. (Frontiers in Astronomy and Space Sciences, 2018)
Observational evidence for the origin of active region magnetic fields has been sought from published information on extended solar cycles, statistical distributions of active regions and ephemeral regions, helioseismology results, positional relationships to supergranules, and fine-scale magnetic structure of active regions and their sunspots during their growth. Statistical distributions of areas of ephemeral and active regions blend together to reveal a single power law. The shape of the size distribution in latitude of all active regions is independent of time during the solar cycle, yielding further evidence that active regions of all sizes belong to the same population. Elementary bipoles, identified also by other names, appear to be the building blocks of active regions; sunspots form from elementary bipoles and are therefore deduced to develop from the photosphere downward, consistent with helioseismic detection of downflows to 3-4 Mm below sunspots as well as long-observed downflows from chromospheric/coronal arch filaments into sunspots from their earliest appearance. Time-distance helioseismology has been effective in revealing flows related to sunspots to depths of 20 Mm. Ring diagram analysis shows a statistically significant preference for upflows to precede major active region emergence and downflows after flux emergence but both are often observed together or sometimes not detected. From deep-focus helioseismic techniques for seeking magnetic flux below the photosphere prior major active regions, there is evidence of acoustic travel-time perturbation signatures rising in the limited range of depths of 42-75 Mm but these have not been verified or found at more shallow depths by helioseismic holographic techniques. The development of active regions from clusters of elementary bipoles appears to be the same irrespective of how much flux an active region eventually develops. This property would be consistent with the magnetic fields of large active regions being generated in the same way and close the same depth as small active regions in a shallow zone below the photosphere. All evidence considered together, understanding the origins of the magnetic fields of solar cycles boils down to learning how and where elementary bipoles are generated beneath the photosphere.